Invasive wild boar's distribution overlap with threatened native ungulate in Patagonia - Bercê, William [UNESP]; Bello, Carolina [UNESP]; Mendes, Calebe P [UNESP]; Vancine, Maurício H [UNESP]; Galetti, Mauro [UNESP]; Ballari, Sebastián A (Oxford University Press (OUP), 2021)
Wild boar (Sus scrofa) is one of the most damaging invasive species in the world and can have a profound impact on the distribution of native species. Nevertheless, there still are limitations on the species' current fine-scale spatial information, which is needed to develop effective management measures. Here, we used Species Distribution Models (SDMs) and niche overlap analysis to estimate potential conflict areas between the wild boar and the native southern pudu (Pudu puda), which is a bioindicator of the forest conservation status within the Nahuel Huapi National Park (NHNP), Argentina. The two species' environmental niche overlaps by 40%, which results in a wide geographical overlap between wild boar and pudu distributions. The distribution model predicted that the wild boar potential distribution occupies 22% of the national park and overlaps up to 67% with the pudu distribution, which in turn occupies 20% of the park. Based on our models, we classified 12% of the park as extreme management priority areas, because both species are present. High priority areas, where wild boars have the potential to invade but will not overlap with pudu populations, represent 10% of the park. Medium priority areas, where wild boars do not threaten pudu populations, and low priority areas, with no potential presence of either species, are 8% and 68%, respectively. The results of this study show how SDMs developed at local scales can support the management and monitoring of native and invasive species and help guide the allocation of efforts and resources for management actions focused on protected areas.
Keywords: conservación; conservation; mammals; mamíferos; manejo de vida silvestre; modelos de distribución de especie; Pudu puda; species distribution modeling; Sus scrofa; wildlife management